Family Support Through Self Care Behavior for Hypertension Patients - Mariyani, Mariyani; Azriful, Azriful; Bujawati, Emmi (Diversity: Disease Preventive of Research Integrity, 2021)
Hypertension has become a major factor in the occurrence of cardiovascular disease worldwide and is still a major challenge in the health sector. Hypertension is a world problem, both on a global and national scale. This study was conducted to determine the relationship between family support and self-care behavior of patients with hypertension. This type of research is quantitative research with an analytic type using a cross-sectional study. The study population consisted of 144 patients in Rappang Village with 106 samples determined using the purposive sampling technique. Collecting data using a questionnaire. The results showed that the appreciation support, emotional support, and instrumental support tended to be good; enough respondent information support and sufficient self-care behavior. Emotional support (p=0.000, RP=2.65), reward support (p=0.001, RP=2.83), informational support (p=0.000, RP=4.27), and instrumental support (p=0.000, RP=12.7), had significant relationship to the patient's self care behavior. It is hoped that the healthcare center can involve families in increasing patient compliance in undergoing treatment and treatment such as involving family support as a health promotion strategy in hypertensive patients.